BASIS NORMAL WEAKLY SELF-DUAL - Irwansyah
Let Fqn and Fq be nite elds with qn and q elements, respectively, where q is a prime power and n is a positive integer. Fqn can be viewed as a vector space over Fq. One important type of bases for Fqn over Fq is self-dual normal bases, because it has many applications in coding theory and cryptography, such as orthogonal transform encoding for cyclic codes and public-key cryptography. Unfortunately, this type of bases exists in some nite elds only, therefore we can't use it in arbitrary nite elds. To avoid this limitation, weakly self-dual normal bases dened, which has similar property as self-dual normal bases and has wider existence. In this thesis, we study the existence and construction of weakly self-dual normal bases.